2002
DOI: 10.1038/sj.bjc.6600548
|View full text |Cite
|
Sign up to set email alerts
|

Detection of peptide-specific CTL-precursors in peripheral blood lymphocytes of cancer patients

Abstract: Development of therapeutic vaccines is one of the major areas of tumour immunotherapy today. However, clinical trials of peptide-based cancer vaccines have rarely resulted in tumour regression. This failure might be due to an insufficient induction of cytotoxic T lymphocytes in the current regimes, in which cytotoxic T lymphocytes-precursors in pre-vaccination peripheral blood mononuclear cells are not measured. Initiation of immune-boosting through vaccination could be better than that of immune-priming with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Stock solutions were diluted with saline just before use. For the peptide screening, prevaccination PBMCs were provided for assays of peptide-specific CTL precursors using methods reported previously (29). Peptide-specific IFN-␥ production was calculated by subtraction of IFN-␥ production of the peptide-stimulated PBMCs in response to a negative control (HIV peptide) from that in response to a corresponding peptide in quadricate assays, and a two-tailed Student's t test was used for the statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Stock solutions were diluted with saline just before use. For the peptide screening, prevaccination PBMCs were provided for assays of peptide-specific CTL precursors using methods reported previously (29). Peptide-specific IFN-␥ production was calculated by subtraction of IFN-␥ production of the peptide-stimulated PBMCs in response to a negative control (HIV peptide) from that in response to a corresponding peptide in quadricate assays, and a two-tailed Student's t test was used for the statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported 14 vaccine candidate peptides that can induce HLA-A24-restriced and tumour-specific CTL in cancer patients (Gomi et al, 1999;Kikuchi et al, 1999;Yang et al, 1999;Harashima et al, 2000;Kawano et al, 2000;Nakao et al, 2000;Nishizaka et al, 2000). We have also shown that most cancer patients have peptide-specific CTL precursors for some of these peptides, and that peripheral blood mononuclear cells (PBMCs) stimulated with positive peptides show HLA-class-I-restricted and tumour-specific cytotoxicity Maeda et al, 2002;Suzuki et al, 2002). In the present study, patients with advanced stages of colorectal cancer were immunised with up to four peptides identified in pre-vaccination measurement of peptidespecific CTL precursors to evaluate the toxicities and responses to CTL precursor-oriented peptide vaccination.…”
mentioning
confidence: 99%
“…Cytotoxicity Assay. The peptide-stimulated PBMCs were incubated for Ͼ21 days, and cytotoxicity was tested by a standard 6-h 51 Cr release assay (17). A two-tailed Student's t test was used for the statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The method used for the detection of peptide-specific CTLs has been reported elsewhere (17). In brief, PBMCs (1 ϫ 10 5 cells/well) were incubated with 10 M of each peptide in the wells of a U-bottomedtype 96-well microculture plate (Nunc, Roskilde, Denmark) in 200 l of culture medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation